Jan-Frans Cantré : Vlaamsch houtsnijder - Philippen, Jos; van den Wijngaert, Frank (Diest : Pro Arte, 1941)
Bibliotheek Jan Baghus
Genummerd exemplaar, dit is nummer 28.
Nederlands
Monografie
Keywords: Cantré, Jan-Frans.; kunst